The Selection of Anode and Cathode Materials for Top Emission Organic Light-Emitting Diodes - Fuh-Shyang Juang; Krishn Das Patel; Kuo-Chun Huang; Wen-Xaing Juang; Jeng-Yue Chen; Lin-Ann Hong (International Journal of Photoenergy)
In this study top emission organic light-emitting diodes (TE-OLED) were successfully fabricated on flexible PET/multilayer disordered silver nanonetwork (MDSN) substrate with conventional LiF/Al as a semitransparent cathode and Ag as a reflective anode. The effects of the hole injection layer, anode buffer layer, and an electron injection layer on the luminescence characteristics of TE-OLEDs were investigated. At first, the thickness of cathode Al is adjusted based upon the overall transmittance of the top-emission cathode and its conductivity. There is a high energy barrier for the hole between the work function of the anode Ag (4.2 eV) and the NPB highest occupied molecular orbital (HOMO) energy level (5.5 eV), which is not favorable for hole injection. This study tested four types of hole injection layer (HIL) materials. Finally, MoO3 was selected as an optimal HIL material, and the optimum thickness was adjusted, enabling the hole to be injected smoothly from the anode to the NPB and then to an emitting layer. The TE-OLED luminance reached 268 cd/m2. There is a high energy barrier between the work function of Ag and MoO3 HOMO (5.3 eV)—about 1.1 eV—which is still not conducive to the hole injection, so a thin layer of high work function metal Au (work function 5.1 eV) was added to the top of the anode silver, which more matches with the MoO3 energy level. It can make the hole easier to inject from the anode to MoO3 (HIL) and protect the silver from oxidation. At 8 V, the luminance is increased to 413.7 cd/m2, and the current efficiency is 0.81 cd/A. The luminance is significantly improved. An electron transport/hole blocking layer TPBi (10 nm) was added to enhance the electron transport capability and effectively block the holes with higher electron mobility and a higher HOMO energy level of TPBi. So that more holes can remain in the emitting layer and increase the chance of the electron-hole recombination to improve the luminance and current efficiency of TE-OLED. At 8 V, the luminance and current efficiency can reach 611.4 cd/m2 and 0.95 cd/A, respectively.